2022
DOI: 10.1039/d2cc05280f
|View full text |Cite
|
Sign up to set email alerts
|

De novoasymmetric Achmatowicz approach to oligosaccharide natural products

Abstract: The development and application of the asymmetric synthesis of oligosaccharides from achiral starting materials is reviewed. This de novo asymmetric approach centers around the use of asymmetric catalysis for the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 179 publications
0
7
0
Order By: Relevance
“…The exploitation of the densely functionalized Achmatowicz dihydropyranones in organic synthesis has been reported in many instances. , The hemiacetal and ketone groups received particular attention as numerous oxidations of the hemiacetal and reductions of the ketone group have been reported. To a lesser extent, the reduction of the olefin has also been described. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of the densely functionalized Achmatowicz dihydropyranones in organic synthesis has been reported in many instances. , The hemiacetal and ketone groups received particular attention as numerous oxidations of the hemiacetal and reductions of the ketone group have been reported. To a lesser extent, the reduction of the olefin has also been described. ,, …”
Section: Introductionmentioning
confidence: 99%
“…12 As shown in Scheme 1c, borate esters demonstrated high reactivity and reacted with four-membered heterocyclic rings directly to form new C−O and C−C bonds without the requirement of transition-metal catalysis, 13 but their application in glycosylation was quite rare. 14 Based on the nature of borate esters, our long-term interest in glycosylation, 15 and previous Pd-catalyzed glycosylation, 16 herein, we report a novel approach to Oglycosylation using 3,4-O-carbonate glycals as the donor and borate esters as the acceptor (Scheme 1d). While 2,3unsaturated-β-O-glycosides were obtained in up to 90% yield under palladium catalysis, 2-deoxy α-O-glycosides were generated in up to 89% yield through copper catalysis at room temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chain compounds are composed of levulinic acid [ 22 , 23 ], diols [ 24 , 25 , 26 ], polyols [ 27 , 28 , 29 ], 2,5-hexanedione [ 30 , 31 , 32 ], and 1-hydroxy-2,5-hexanedione [ 31 , 32 , 33 , 34 ], which are all valuable chemicals with a wide range of application. Ring compounds contain non-furan heterocycles [ 35 , 36 , 37 , 38 ] and carbon rings. In 2012, Hronec et al [ 39 ] first reported the conversion of furfural to cyclopentanone (CPO), and then Ohyama et al [ 40 ] realized the transformation of HMF to a cyclopentanone derivative, 3-hydroxymethylcyclopentanone (HCPN).…”
Section: Introductionmentioning
confidence: 99%